Evaluation of microbiological parameters in arroyo Santa María, Jalpa de Méndez, Tabasco, México - Cárdenas-Córdova, María Elena (2024)
Faecal contamination of surface water bodies causes negative impacts on health and the environment worldwide in underdeveloped countries. The objective of the following study was to evaluate the microbiological quality of the water from the Santa María de Jalpa de Méndez, Tabasco, Mexico. Three sampling stations were established along the stream at different depths (30 and 60 cm). Station one, was located in the opposite direction to the mouth of the stream in a river known as Los Caballos, the second, in the middle of the stream and the third where the stream emptied into the river. The microbiological parameters evaluated were Faecal Coliforms (CF) and Total Coliforms (TC). For the sampling and analysis of CT and CF, the recommendations and method of the most probable number in multiple tubes according to NMX-AA-042-SCFI-2015 respectively were used. A 3 x 2 factorial variance analysis was carried out to find statistically significant differences between the different sampling stations and depths. The three stations showed minimum and maximum mean values of CF and TC (650 to 1131 and 712 to 1225 MPN / 100 ml respectively) higher than the limits established by ecological criteria CE-CCA-001/89 (> 200 MPN / 100 ml) . In fact, it does not comply with the maximum permissible limits of the Mexican standard for human consumption NOM-127-SSA1-1994 (2 NMP / 100 ml). The Santa María stream presents high concentrations of faecal contamination that directly impacts the health of the people near the stream and the environment.